Waste Sorting and Processing Training for Rhizome Plant Fertilizer as an Effort to Introduction of the Circular Economy Concept in the Penggilingan Village: Pelatihan Pemilahan dan Pengolahan Sampah untuk Pupuk Tanaman Rimpang sebagai Upaya Pengenalan Konsep Ekonomi Sirkular di Kelurahan Penggilingan - Louis Valenthenardo; Katherine; Sulkhan Windrayahya; Junaida Astina; Priscilla K. Adhiwijaya; Desak PAP. Dewi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
In 2022, DKI Jakarta produced 7,500 tons of waste per day, which caused the Integrated Waste Management Facility Bantar Gebang to be nearly full. Waste reduction can be achieved by the people of DKI Jakarta through waste separation and independent waste processing. The low awareness of waste separation leads some people to consider it unhelpful and a waste of time. The goal of this activity is to increase knowledge about waste separation and composting through socialization and training in the Penggilingan Sub-district of Cakung, East Jakarta. Additionally, this activity aims to introduce the concept of a circular economy to the people of Penggilingan, where the compost produced can be used as fertilizer for planting rhizomes. The results of this activity show that there was an increase in the awareness and skills of the Penggilingan community from 65.56% (pre-test) to 91.74% (post-test). Furthermore, the community found this training beneficial and enlightening, as indicated by the evaluation results of 3.84/4.00. This demonstrates the importance of training for the community to enhance their awareness and skills.